An Assessment of the Water Table Dynamics in a Constructed Wetland, Fort McMurray, Alberta - Spennato, Haley (My University, 2016)
Oil sand mining removes the wetland and forestlands of the Boreal Plains, and replaces this landscape with open pits, tailings ponds and overburden piles to access the oil-bearing formations below. In turn, mine regulators are forced to reclaim the disturbed, post-mined land to pre-disturbance conditions. In 2012, Syncrude Canada Limited (SCL) constructed one of the first of two reclaimed wetlands, the Sandhill Fen Watershed (SFW), to evaluate wetland reclamation strategies. SFW is a 52-ha system atop soft-tailings that includes an inflow/outflow pump system, underdrains, upland hummock areas, and a fen lowland. This study examines trends in water table position and lateral gradients that are developing, as well as observe system response to pump management. Spanning May- Oct 2014 and 2015, precipitation was measured at three meteorological stations across the fen, artificial inflows and outflows were recorded using a series of pumps, and water table position was measured using a network of 27 near-surface wells instrumented with transducers. Water table was maintained near the peat surface for both study seasons, indicating the potential for maintenance of wetland conditions. Though data is limited, upland-lowland interactions are beginning to develop, suggesting the uplands are beginning to supply water to the lowland fen. Flow reversals are reported along the fen lowland in dry periods, and the east and west fens become hydrologically disconnected as the season progresses. Comparison with analogue sites provides reference for hydrologic processes within SFW and provides insight on the influence of pump management on the system.